Modernity and the Idea of Progress - Mouzakitis, Angelos (Frontiers in Sociology, 2017)
This paper aims to show the centrality the concept of progress occupies explicitly and implicitly in social theory, in relation to the theorization and understanding of modernity; it also raises the question whether in times where Eurocentrism, logocentrism and indeed almost every claim of supremacy are rightly viewed with suspicion, it is possible to think of modernity without relying on some interpretation of the notion of progress. Arguably, the theme of progress, together with the complementary notion of decline, can be considered as a key-component of discourses concerning modernity and has played a major role in the shaping of social theory. Comte and Durkheim relied in different ways in the idea of progress and the same holds for Marxist accounts of social change. Even later sociological theories address modernity from the perspective of progress, Parsons being exemplary in this respect. Moreover, theoretical discourses adopting a critical or even hostile attitude against the modern project often question the idea of progress and are woven around the representation of modernity in terms of decline and regression into unreason, as e.g. Adorno and Horkheimer’s Dialectic of Enightment. Arguably, the imagery of progress informs the distinction between society and community, which is also hidden behind Habermas’s more recent theorization of societies in terms of systems and lifeworlds. Finally, the question regarding the possibility of partially disentangling the theorization of modernity from the idea of progress, is pursued via a critical assessment of Eisenstadt's multiple modernities and Wagner's theorization of modernity in terms of responses given to basic problématiques.